Data Security in Indonesia: Bibliometric Analysis of the Development of Personal Data Regulatory - Hanna Nurhaqiqi; Ratih Pandu Mustikasari; Kusnarto (LPPM Stikosa - AWS, 2023)
The Regulation on Personal Data Protection was passed at the end of 2022. Personal data is very significant in this modern era. The world of communication today is closely related to personal data. The internet network makes data an expensive and invaluable asset. Many journals research personal data and current problems. This study identifies and analyzes research developments regarding the Regulation of Personal Data. Data were obtained from 200 journals from Google Scholar using Publish or Perish software in the last five years. This data is then visualized through the Vos Viewer software. The results found are seven clusters, 35 items, and 284 links. The keywords that appear are Privacy, Data Privacy, Data, Security and so on. If there was more research on Data Security on Blockchain in the previous five years, now the research trend is more on Privacy Concerns, Users, and Personal Data.